Testicular cancer survivors have shorter anogenital distance that is not increased by 1 year of testosterone replacement therapy. Issue 9 (5th July 2021) - Priskorn, L; Kreiberg, M; Bandak, M; Lauritsen, J; Daugaard, G; Petersen, J H; Aksglaede, L; Juul, A; Jørgensen, N
Abstract: STUDY QUESTION: Is anogenital distance (AGD) shorter in testicular cancer (TC) survivors than in men from the general population, and is AGD affected by testosterone replacement therapy in adulthood? SUMMARY ANSWER: AGD, measured as distance from anus to scrotum (AGDas), is shorter in TC survivors and does not change as a result of testosterone replacement therapy. WHAT IS KNOWN ALREADY: Animal studies have shown that AGD is a postnatal 'read-out' of foetal androgen action, and short AGD in male offspring is considered a sign of feminization caused by in utero disruption of the reproductive system. Likewise, measurement of AGD in human studies has suggested AGD to be part of the testicular dysgenesis syndrome hypothesis, which proposes that male reproductive disorders, such as hypospadias, cryptorchidism, some cases of impaired semen quality and TC, all share a common foetal origin. STUDY DESIGN, SIZE, DURATION: The aim was to assess AGD in men with a history of TC and controls, and furthermore to examine AGD during testosterone replacement therapy in adulthood. Study participants were TC survivors with a mild Leydig cell insufficiency who participated in a randomized double-blind study of testosterone replacement therapy versus placebo for 52 weeks (N = 69). Men from the general population were prospectively included from a study on testicular function as controls (N = 67). PARTICIPANTS/MATERIALS, SETTING, METHODS: We measured two variants of AGD; as our primary outcome the anoscrotal distance (AGDas) measured from the centre of the anus to the posterior base of the scrotum, and secondarily the anopenile distance (AGDap) measured from the anus to the cephalad insertion of the penis. Using multiple regression analysis, the mean difference in AGD between TC survivors and men from the general population was assessed, adjusted for height, BMI and examiner. Next, AGD was measured before and after 52 weeks of treatment with testosterone or placebo, and with covariance analysis differences between the two groups at follow-up was assessed after adjustment for baseline AGD, examiner, BMI and change in BMI during treatment. MAIN RESULTS AND THE ROLE OF CHANCE: TC survivors had a shorter AGDas (−0.84 cm, 95% CI: −1.31; −0.37) compared to men from the general population, and AGDas did not differ between the testosterone and placebo treated group at follow-up (0.11 cm, 95% CI: −0.22; 0.44). In contrast, AGDap was not shorter in TC survivors after adjustment (0.05 cm, 95% CI: −0.30; 0.39), and was 0.48 cm longer (95% CI: 0.13; 0.82) at follow-up in the testosterone treated compared to the placebo-treated group. LIMITATIONS, REASONS FOR CAUTION: A limitation of the study is that the number of included men was limited, and results need confirmation in a larger study. Furthermore, TC survivors were significantly older than controls. For the comparison of AGD in TC survivors and controls, it was not possible to conduct the examinations with the examiner being blinded to which group he was examining, and it cannot be excluded that this can cause a bias. WIDER IMPLICATIONS OF THE FINDINGS: The shorter AGDas in TC survivors compared to controls, which did not change upon adult testosterone replacement therapy, supports the hypothesis that reduced AGD is part of the testicular dysgenesis syndrome and may be a marker of disrupted foetal testicular development. By contrast, AGDap was not shorter in TC survivors and might be modestly sensitive to adult testosterone treatment, and thus inferior to AGDas as a constant postnatal marker of the foetal androgen environment. STUDY FUNDING/COMPETING INTEREST(S): Expenses were paid by the Department of Oncology, Copenhagen University Hospital, Rigshospitalet. Kiowa Kirin International covered expenses for Tostran and placebo. The Danish Cancer Society, The Danish Cancer Research Foundation, the Preben & Anna Simonsen Foundation, and Rigshospitalet have supported the study. L.P. was financed by the Research Fund of the Capital Region of Denmark. The authors have no competing interests. TRIAL REGISTRATION NUMBER: Part of the study is based on men participating in a randomized controlled trial registered at ClinicalTrials.gov, NCT02991209, 25 November 2016.